Five Year Plan Progress Report for 1953-54 - Planning Commission, Government of India (Planning Commission, Government of India, 1954)
This Progress Report is concerned primarily with the working of the Five Year Plan during the year 1953-54; but opportunity has been taken to review, so far as possible, the achievements of the first 3 years in relation to the targets set for 1955-56. Although, strictly speaking, the period covered by the Report ended on March 31st, 1954, mention has been made of developments since that date wherever this appeared to be appropriate.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Five Year Plan Progress- India; Economic and Social Development